2023
DOI: 10.3758/s13428-022-02042-9
|View full text |Cite
|
Sign up to set email alerts
|

A state response measurement model for problem-solving process data

Abstract: In computer simulation-based interactive tasks, different people make different response processes to the same tasks, resulting in various action sequences. These sequences contain rich information, not only about respondents, but also about tasks. In this study, we propose a state response (SR) measurement model with a Bayesian approach for analyzing the process sequences, which assumes that each action made is determined by the individual's problem-solving ability and the easiness of the current problem stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For instance, Scoular et al [ 23 ] and Drake et al [ 24 ] have demonstrated how student behavior from log file data, can be scored to assess performance in collaborative problem-solving tasks. And various models have been developed to estimate problem-solving abilities from action sequences [ 25 , 26 ] and student speed from action time [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Scoular et al [ 23 ] and Drake et al [ 24 ] have demonstrated how student behavior from log file data, can be scored to assess performance in collaborative problem-solving tasks. And various models have been developed to estimate problem-solving abilities from action sequences [ 25 , 26 ] and student speed from action time [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Process data, on top of final scores, offer a wealth of information about individual differences, test-taking engagement, and the steps examinees take to reach their final response. Studies have demonstrated the utility of process data for a multitude of practical tasks: To start, process data can provide additional information on the measured proficiency or skills, allowing better measurement via process-incorporated scoring rules (Zhang et al, 2023) and process-based measurement models, which typically associate continuous latent proficiency (Chen, 2020; Han et al, 2022; LaMar, 2018; Liu et al, 2018; Xiao & Liu, 2024) or discrete latent skill mastery (Zhan & Qiao, 2022; Liang et al, 2022) with examinees’ choices of correct/incorrect subsequent actions, observed action subsequences, or sequence length. Furthermore, analyses of behavioral characteristics associated with successful/unsuccessful final performance (e.g., Gao, Cui, et al, 2022; Gao, Zhai, et al, 2022; Greiff et al, 2015; He & von Davier, 2016; Qiao & Jiao, 2018; Qiao et al, 2023; Ulitzsch et al, 2021, 2023) can inform test validation and automated scoring.…”
mentioning
confidence: 99%